Andropov’s Gamble: Samantha Smith and Soviet Soft Power - Fedyashin, Anton (Journal of Russian American Studies, 2020)
General Secretary Yuri Andropov’s recourse to cultural and public diplomacy through the family of Samantha Smith in 1983 constituted the last attempt of an entrenched regime to salvage itself through a peace offensive without reforming its fundamental structure. With its ideological magnetism spent, the Soviet government made a last-ditch effort at popular détente that aimed to outmaneuver the Reagan and Thatcher rhetoric. However, Andropov’s attempt to decouple Soviet foreign aspirations from his government’s domestic policies rendered his public relations gamble highly vulnerable. Ironically, Andropov’s PR gamble produced the greatest results in the Soviet Union when it became sufficiently free to take advantage of them under Gorbachev.